1996
DOI: 10.1113/expphysiol.1996.sp003973
|View full text |Cite
|
Sign up to set email alerts
|

Inward rectification of the large conductance potassium channel in smooth muscle cells from rabbit pulmonary artery

Abstract: Large conductance Ca(2+)-dependent K+ channels were studied in smooth muscle cells enzymatically dissociated from rabbit pulmonary artery. The current-voltage relationship of single channels recorded in cell-attached patches revealed strong inward rectification, which disappeared after patch excision. Cell permeabilization with saponin, beta-escin or equinatoxin II also removed rectification. These observations imply the existence of fast open channel block by an intracellular substance(s). Application to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…When single BK channel recordings were taken from intact myocytes, we found that the value of the outward current was significantly less than that recorded from excised patches, a finding in line with previous reports [28,44]. In particular, the current was markedly reduced at high voltages (presumably due to the high voltage-dependent block of intracellular polyamines, and Mg and Na ions [11,28,44]), whereas only minor inhibition (smaller than 30%) of the current was observed at physiologically relevant membrane potentials.…”
Section: General Characteristics Of the Bk Channelsupporting
confidence: 89%
See 1 more Smart Citation
“…When single BK channel recordings were taken from intact myocytes, we found that the value of the outward current was significantly less than that recorded from excised patches, a finding in line with previous reports [28,44]. In particular, the current was markedly reduced at high voltages (presumably due to the high voltage-dependent block of intracellular polyamines, and Mg and Na ions [11,28,44]), whereas only minor inhibition (smaller than 30%) of the current was observed at physiologically relevant membrane potentials.…”
Section: General Characteristics Of the Bk Channelsupporting
confidence: 89%
“…In cell-attached patches BK channel conductance was smaller than that recorded following excision of the patch. This observation has been already documented for BK channels in other smooth muscle tissues [28,44], and interpreted to be due to voltage-dependent block of the BK channel by intracellular Mg and Na ions, and polyamines. This behaviour is illustrated in Fig.…”
Section: Single Bk Channel Recordings From Intact Myocytesmentioning
confidence: 54%
“…BK channels of rabbit pulmonary smooth muscle in contrast to other cells exhibit strong rectification (Snetkov et al, 1996). This was attributed to the presence of spermine and spermidine but not putrescine in the cytoplasm.…”
Section: Bk Channels -And Polyaminesmentioning
confidence: 96%
“…In smooth muscle cells from rabbit pulmonary artery EqT II and other permeabilizing agents caused removal of inward rectification in large conductance Ca 2+ -activated potassium channels that could not be explained by pore-formation and cell permeabilization (Snetkov et al 1996). It is well established that pore formation in erythrocytes requires at least 0.1 nM, but in most other cells at least 100 nM EqT II.…”
Section: A Wide Range Of Effects Of Eqt II On Regulatory Membrane Promentioning
confidence: 98%